The evolution of femoral morphology in giant non-avian theropod dinosaurs - Pintore, Romain; Hutchinson, John R.; Bishop, Peter J.; Tsai, Henry P.; Houssaye, Alexandra (Paleobiology, 2024)
Theropods are obligate bipedal dinosaurs that appeared 230 Ma and are still extant as birds. Their history is characterized by extreme variations in body mass, with gigantism evolving convergently between many lineages. However, no quantification of hindlimb functional morphology has shown whether these body mass increases led to similar specializations between distinct lineages. Here we studied femoral shape variation across 41 species of theropods (n = 68 specimens) using a high-density 3D geometric morphometric approach. We demonstrated that the heaviest theropods evolved wider epiphyses and a more distally located fourth trochanter, as previously demonstrated in early archosaurs, along with an upturned femoral head and a mediodistal crest that extended proximally along the shaft. Phylogenetically informed analyses highlighted that these traits evolved convergently within six major theropod lineages, regardless of their maximum body mass. Conversely, the most gracile femora were distinct from the rest of the dataset, which we interpret as a femoral specialization to “miniaturization” evolving close to Avialae (bird lineage). Our results support a gradual evolution of known “avian” features, such as the fusion between lesser and greater trochanters and a reduction of the epiphyseal offset, independent from body mass variations, which may relate to a more “avian” type of locomotion (more knee than hip driven). The distinction between body mass variations and a more “avian” locomotion is represented by a decoupling in the mediodistal crest morphology, whose biomechanical nature should be studied to better understand the importance of its functional role in gigantism, miniaturization, and higher parasagittal abilities.
Keywords: dept.bio; open-access; peer-reviewed

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Conner, L.M.; Goedert, D.; Fitzpatrick, S.W.; Fearnley, A.; Gallagher, E.L.; Peterman, J.D.; Forgione, M.E.; Kokosinska, S.; Hamilton, M.; Masala, L.A.; Merola, N.; Rico, H.; et al. (Chemosphere, 2024)
Human impacts on wild populations are numerous and extensive, degrading habitats and causing population declines across taxa. Though these impacts are often studied individually, wild populations typically face suites of stressors acting concomitantly, compromising the fitness of individuals and populations in ways poorly understood and not easily predicted by the effects of any single stressor. Developing understanding of the effects of multiple stressors and their potential interactions remains a critical challenge in environmental biology. Here, we focus on assessing the impacts of two prominent stressors associated with anthropogenic activities that affect many organisms across the planet – elevated salinity (e.g., from road de-icing salt) and temperature (e.g. from climate change). We examined a suite of physiological traits and components of fitness across populations of wood frogs originating from ponds that differ in their proximity to roads and thus their legacy of exposure to pollution from road salt. When experimentally exposed to road salt, wood frogs showed reduced survival (especially those from ponds adjacent to roads), divergent developmental rates, and reduced longevity. Family-level effects mediated these outcomes, but high salinity generally eroded family-level variance. When combined, exposure to both temperature and salt resulted in very low survival, and this effect was strongest in roadside populations. Taken together, these results suggest that temperature is an important stressor capable of exacerbating impacts from a prominent contaminant confronting many freshwater organisms in salinized habitats. More broadly, it appears likely that toxicity might often be underestimated in the absence of multi-stressor approaches. © 2024 Elsevier Ltd
Keywords: Amphibians; Climate change; Local adaptation; Maladaptation; Pollution; Road salt; dept.bio; peer-reviewed

Gross and microanatomic description of the dental pads of the Florida manatee, Trichechus manatus latirostris, and their importance to mastication - Barboza, Meghan; Kallaway, Kiara (Archives of Oral Biology, 2024)
Objective Florida manatee feeding ecology is critical to species survival, but the role of dental pads in feeding has received limited attention. This study characterized the gross and microscopic anatomy of the manatee’s dorsal and ventral dental pad in relation to these structures’ importance in mastication, which furthers our understanding of manatee feeding and health. Design Whole heads from 6 animals (4 male and 2 female) of varying sizes were examined grossly. Sections (5 µm) from throughout the dorsal and ventral dental pads were stained with Hematoxylin and Eosin to document microanatomy. The thickness of the epithelium and stratum corneum were measured. Results The ventral dental pad epidermal (1129–3391 µm) and stratum corneum (331–1848 µm) thickness increased with increased body size. The dorsal dental pad epidermal (690–1988 µm) and stratum corneum (121–974 µm) thickness varied relative to size. The dental pad anatomy, including the thickened stratum corneum, indicates an importance similar to molars in grinding and physically breaking up plant material. Extensive appendages including filiform-like papillae and well-developed rete were observed and likely provide physical support for mastication. Conclusion While the sample size limits specific conclusions based on sex or age, it provides a good overview of the anatomy of the dental pads. The manatee is the only mammal known to have a ventral dental pad and the well-developed grinding surfaces demonstrates a crucial role in mastication for these structures. These dental pads should be evaluated during health checks and necropsies and considered in future research on manatee’s feeding mechanisms.
Keywords: Dental pad; Florida manatee; Hard palate; Keratinization; Mastication; Stratum corneum; dept.bio; peer-reviewed

Sea urchin Arbacia punctulata feeding preference for algal turf over kelp in a degraded kelp forest ecosystem - Kelly, Sophia R.; Hamel, Kenneth; Narvaez, Carla A.; Armstrong, Thomas J.; Grace, Sean P.; Feehan, Colette J. (Journal of Experimental Marine Biology and Ecology, 2024)
Climate change is driving a shift in the distribution of global kelp forests, with the contraction of kelp habitats occurring at warm range edges. Declining kelps often have been replaced by novel algal turf assemblages, which are reinforced by ecological feedback mechanisms and provide fewer ecosystem services. Trophic interactions among marine herbivores, algal turfs, and kelps on algal turf-dominated reefs remain poorly resolved but could have important implications for the stability of algal turf reefs and the potential for kelp forest recovery. Here, we examine herbivory by the Atlantic purple sea urchin, Arbacia punctulata, in a degraded kelp forest ecosystem dominated by algal turf in southern New England, USA. In a localized field survey, we observed lower algal turf cover on reef areas containing A. punctulata (mean ± SE: 62 ± 12% turf cover) as compared to areas with no sea urchins present (92 ± 4% turf cover). Reef areas with and without sea urchins had similarly low cover of the previously dominant kelp, Saccharina latissima (6–8% kelp cover). In laboratory and field experiments, individuals or groups of A. punctulata enclosed with a diet choice of algal turf versus kelp had higher grazing rates on the algal turf. A. punctulata in the laboratory also exhibited greater attraction to algal turf over kelp, physically moving towards this food source. In combination, the results provide evidence that A. punctulata has a feeding preference for algal turf over kelp in southern New England. Future research is warranted to further examine the grazing ecology of A. punctulata, particularly in the context of ongoing kelp forest restoration efforts in this region.
Keywords: Herbivory; Northwest Atlantic; Regime shift; Restoration; SCSU-student; dept.bio